Acute myeloid leukaemia with myelodysplasia-related change in a child living with human immunodeficiency virus infection, a transformation from underlying juvenile myelomonocytic leukaemia - Vongai Mashoko; Diane Mackinnon; Jenifer Vaughan (South African Journal of Oncology, 2020)
Juvenile myelomonocytic leukaemia (JMML) is an aggressive clonal haematopoietic disorder that presents in early childhood. It is classified by the World Health Organization (WHO) as an overlap myeloproliferative or myelodysplastic disorder. The pathogenesis of JMML has been well-explained at the molecular level using clear diagnostic criteria. There is limited literature on JMML in the context of HIV infection. The only curative modality for the majority of patients with JMML is allogeneic haematopoietic stem cell transplant (HSCT). The role of other chemotherapeutic approaches is to ameliorate the disease but they are no substitute for allogeneic HSCT. We report a case of a 59-month-old child with vertically transmitted HIV-infection who was referred to the authors’ institution for further management.